Ganglioside promotes the bridging of sciatic nerve defects in cryopreserved peripheral nerve allografts - Wang, Yaodong (Neural Regen Res, 2014)
Previous studies have shown that exogenous gangliosides promote nervous system regeneration and synapse formation. In this study, 10 mm sciatic nerve segments from New Zealand rabbits were thawed from cryopreservation and were used for the repair of left sciatic nerve defects through allograft bridging. Three days later, 1 mL ganglioside solution (1 g/L) was subcutaneously injected into the right hind leg of rabbits. Compared with non-injected rats, muscle wet weight ratio was increased at 2–12 weeks after modeling. The quantity of myelinated fibers in regenerated sciatic nerve, myelin thickness and fiber diameter were elevated at 4–12 weeks after modeling. Sciatic nerve potential amplitude and conduction velocity were raised at 8 and 12 weeks, while conduction latencies were decreased at 12 weeks. Experimental findings indicate that ganglioside can promote the regeneration of sciatic nerve defects after repair with cryopreserved peripheral nerve allografts.